Development of Virtual Mentor-Based Chembo Learning Media to Improve The Learning Outcomes of Science Education Students - Mellyta Uliyandari; Nirwana Nirwana; Sutarno Sutarno (Universitas Lambung Mangkurat, 2023)
This study aims to develop Chembo (Chemical Bond) learning media based on Virtual Mentors to improve student learning outcomes in Science Education on Chemical Bonds. The research method used is research and development with 4D (four-D) design, namely definition, design, development, and deployment. The instruments used in this research were questionnaires and pretest and posttest questions. The results of the study show that the results of material validation by material experts are at number 72 which is in the